Strategi Guru PAI : Problematika dan Solusi Peningkatan Prestasi Belajar Peserta Didik: - waluyo erry wahyudi; Khairunnisa; Ahmad Fatoni; Sa'idy (Kopertais Wilayah XV Lampung, 2022)
Learning strategies are approaches that a teacher selects and employs when delivering instructional materials with the goal of facilitating students' assimilation and comprehension of those materials so that, ultimately, the learning objectives can be mastered at the conclusion of learning activities. There were still pupils at Mutiara Bangsa Middle School in Bandar Lampung who scored below the KKM, which was an issue for the school. Islamic religious education teachers there also used the learning technique to improve learning results. Therefore, study is required to understand the teaching methods used by Islamic religious education instructors at Mutiara Bangsa Middle School in Bandar Lampung to improve student learning outcomes as well as the barriers to using these methods. This is a qualitative study that employs the qualitative descriptive method. Using observations, interviews, and documentation. While data analysis techniques go through four stages, namely data collection, data reduction, data presentation and conclusions. The results of this study indicate that the learning strategy of Islamic religion teachers to improve learning achievement at Mutiara Bangsa Middle School in Bandar Lampung is quite good. The conclusion from this study is that the strategies used by Islamic Religious Education teachers to improve learning achievement are direct learning strategies, indirect learning strategies, interactive learning strategies, experiential learning strategies, and independent learning strategies. In terms of learning achievement in Islamic religious education, the majority has increased and improved. There are still impediments to its implementation, such as a lack of interest in Islamic religious education, the fact that students only participate in the learning process, and the extremely limited time available for Islamic religious education learning.